PENGARUH SUPERVISI KEPALA SEKOLAH DAN PENGEMBANGAN TENAGA PENDIDIK TERHADAP KINERJA GURU MADRASAH ALIYAH SWASTA DI KABUPATEN LIMA PULUH KOTA - Maulid, Ahmad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
This quantitative research of causal design was aimed at testing the effect of principal’s supervision towards teachers’ performance of Madrasah Aliyah Swasta in Lima Puluh Kota. The population were 172 teachers. The sample were taken by using Sloviv formula. The data were collected by using questionnaire Likert scale. The data were analyzed by using double linear regresion, Ftest, ttest dan Rtest. The results obtained indicate that 1) there was positive significant effect of principal’s supervision towards teachers’ performance; 2) no significant effect of teachers’ professional development towards teachers’ performance; 3) the principal’s supervision and teachers’ professional development gave significant effect towards teachers’ performance (sig) < 0,05. Based on the coeficient analysis, the principal’s supervision and teachers’ professional development gave effect 17.8% towards teachers’ performance of Madrasah Aliyah Swasta in Lima Puluh Kota and 82,2% from another variable which was not discussed in this research. Keywords: Principal’s Supervision, Teachers’ Professional Development, Teachers’ Performance, Madrasah Aliyah Swasta, Lima Puluh Kota